Optimalisasi UMKM di Kevikepan Surakarta: Strategi Pemasaran Melalui Meta Ads - Jati, Intan Mustika; Serenade, Vincensia; Gusniar, Bella; Wicaksono, Nicky Gilang; Astuti, Annisa Puji (Amirul Bangun Bangsa, 2025)
Workshop